2014
DOI: 10.1039/c4sm00683f
|View full text |Cite
|
Sign up to set email alerts
|

Melt crystallization/dewetting of ultrathin PEO films via carbon dioxide annealing: the effects of polymer adsorbed layers

Abstract: The effects of CO2 annealing on the melting and subsequent melt crystallization processes of spin-cast poly(ethylene oxide) (PEO) ultrathin films (20-100 nm in thickness) prepared on Si substrates were investigated. By using in situ neutron reflectivity, we found that all the PEO thin films show melting at a pressure as low as P = 2.9 MPa and at T = 48 °C which is below the bulk melting temperature (Tm). The films were then subjected to quick depressurization to atmospheric pressure, resulting in the non-equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 84 publications
3
53
0
1
Order By: Relevance
“…The choice of the two‐layer model was determined by the corresponding FT profile of the XR profile, and the details of the data analysis have been described elsewhere . The densification of the polymer chains in the vicinity of the substrate surface is in line with previous experimental and simulation findings . The presence of the two‐layer formation indicates that the irreversible adsorption of polymer chains on a solid surface is kinetically controlled: the later arriving polymer chains “reel‐in” the empty spaces of the flattened layer, forming the outer loosely adsorbed polymer chains on the solid surface.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The choice of the two‐layer model was determined by the corresponding FT profile of the XR profile, and the details of the data analysis have been described elsewhere . The densification of the polymer chains in the vicinity of the substrate surface is in line with previous experimental and simulation findings . The presence of the two‐layer formation indicates that the irreversible adsorption of polymer chains on a solid surface is kinetically controlled: the later arriving polymer chains “reel‐in” the empty spaces of the flattened layer, forming the outer loosely adsorbed polymer chains on the solid surface.…”
Section: Resultsmentioning
confidence: 62%
“…Since irreversible polymer adsorption takes place even when a polymer–solid interaction is weak, the formation of an adsorbed layer at the interface is almost unavoidable when a thin polymer film is annealed at temperatures far above the bulk glass transition temperature ( T >> T g ). Recent studies have shown that the irreversible adsorption of polymer chains at the polymer–solid interface leads to significant deviations in the physical and mechanical properties of thin polymer films, including glass transition, thermal expansivity, local viscosity, interdiffusion, thermal stability, and crystallization processes, relative to their bulk counterparts. Moreover, although the adsorbed layer is typically much thinner than the unperturbed radius of polymer gyration ( R g ), the effect can propagate several tens of nanometers into the film interior …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is found from many studies on the crystallization behavior that the crystallinity of block chains confined in nanolamellae increases sigmoidally with a finite induction time, indicating that the crystallization is virtually driven by a combined mechanism of heterogeneous nucleation and subsequent crystal growth. Because a comprehensive understanding of the detailed crystallization mechanism of homopolymers confined in nanolamellae is directly applicable to the surface crystallization of homopolymers [88][89][90][91][92] or crystallization within thin films [93][94][95][96][97][98], it is essential to examine the crystallization of homopolymers (and also block chains) confined in various nanolamellae.…”
Section: Nanolamellaementioning
confidence: 99%
“… 20 31 Depending on the polymer characteristics and thermal processing history, polymer chains that directly interact with the substrate surface via physisorption can possess different chain conformation, adsorbed amount, surface coverage, and density on the substrate. 20 , 21 , 24 , 26 28 , 30 , 32 Recent studies have revealed a strong correlation between autophobic dewetting of thin polymer films and the nanoarchitectures/conformations of adsorbed chains at the interface, where the conformational difference between the adsorbed chains and free chains plays a significant role. 25 , 29 31 Interestingly, by using the top-down solvent leaching method (also known as Guiselin’s approach), 33 it has been found that cyclic PS melt forms thicker irreversibly adsorbed layers on solid substrates than the linear PS melt, which can dramatically alter the interfacial effect on chain dynamics and dewetting behaviors of polymer thin films.…”
Section: Introductionmentioning
confidence: 99%